Analytical Method Validation of Sildenafil Citrate and Caffeine in Herbal Medicine for Increasing Stamina using Thin Layer Chromatography – Densitometry - Rena Octaria; Diana Diana; Henry Kurnia Setiawan (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Traditional medicine has been trusted for generations as an effective remedy for various health conditions and is widely recognized for its safety when compared to synthetic pharmaceuticals. One of the main reasons individuals choose herbal medicines is their relative affordability and the perception that they are free from harmful chemical additives. However, recent public warnings issued between 2020 and 2025 have revealed the presence of hazardous medicinal chemicals (Bahan Kimia Obat/BKO) such as sildenafil citrate and caffeine in some stamina-enhancing herbal products. This study aims to develop and validate an analytical method using Thin Layer Chromatography (TLC) coupled with densitometry for the detection of sildenafil citrate and caffeine in herbal medicines. The method was chosen due to its simplicity, low operational cost, and ability to effectively separate these two compounds. A category II validation was performed to determine the presence of impurities, with a focus on parameters including selectivity and the Limit of Detection (LOD). The mobile phase employed was a combination of chloroform and ethanol (9.5:0.5 v/v), and detection was carried out at 254 nm using a densitometer. The TLC results showed that sildenafil citrate and caffeine had Rf values of 0.32 and 0.52, respectively, with a resolution (Rs) of 2, indicating a good separation. The LOD for sildenafil citrate was 8.5418 μl/ml (0.0854 mg per 600 mg sample), while the LOD for caffeine was 4.7987 μl/ml (0.0959 mg per 600 mg sample). These findings highlight the importance of routine quality control testing to ensure the safety and authenticity of herbal medicines in the market.